31.2k views
4 votes
Solve using elimination
3x+3y=27
x-3y= -11

1 Answer

1 vote

Answer:

(4, 5)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Property

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define systems

3x + 3y = 27

x - 3y = -11

Step 2: Solve for x

  1. Eliminate y (add equations): 4x = 16
  2. Divide 4 on both sides: x = 4

Step 3: Solve for y

  1. Define original equation: x - 3y = -11
  2. Substitute in x: 4 - 3y = -11
  3. Subtract 4 on both sides: -3y = -15
  4. Divide -3 on both sides: y = 5
User Yuvaraja
by
5.7k points